2010
DOI: 10.1016/j.ajhg.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Brown-Vialetto-Van Laere Syndrome, a Ponto-Bulbar Palsy with Deafness, Is Caused by Mutations in C20orf54

Abstract: Brown-Vialetto-Van Laere syndrome is a rare neurological disorder with a variable age at onset and clinical course. The key features are progressive ponto-bulbar palsy and bilateral sensorineural deafness. A complex neurological phenotype with a mixed picture of upper and lower motor neuron involvement reminiscent of amyotrophic lateral sclerosis evolves with disease progression. We identified a candidate gene, C20orf54, by studying a consanguineous family with multiple affected individuals and subsequently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 14 publications
6
179
0
3
Order By: Relevance
“…99 This syndrome is closely related to Fazio-Londe syndrome, in which auditory function is spared. 3 …”
Section: Als With Deafnessmentioning
confidence: 99%
“…99 This syndrome is closely related to Fazio-Londe syndrome, in which auditory function is spared. 3 …”
Section: Als With Deafnessmentioning
confidence: 99%
“…Cases of secondary MADD related to riboflavin deficiency have been described in neonates of mothers carrying heterozygous mutations in a riboflavin transporter (deficiency for GPR172B/SLC52A1) and showed a good response to transient riboflavin supplementation (Chiong et al 2007;Harpey et al 1983;Ho et al 2011). A different entity with later presentation, Brown-Vialetto-Van Laere syndrome, is caused by mutations in two related riboflavin transporters SLC52A2 and SLC52A3 (Bosch et al 2011;Green et al 2010;Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 Green et al reported that a C20orf54 gene mutation causes Brown-Vialetto-Van Laere syndrome. 10 Although there is no definitive evidence for a causative role of this gene in 12 Riboflavin is a precursor of flavin adenine dinucleotide and flavin mononucleotide, which in turn are electron acceptors important in cell metabolism. Riboflavin is essential for cellular energy generation and DNA repair, and is a plausible candidate for a maintenance role in nervous system function.…”
Section: Discussionmentioning
confidence: 99%